MENILAI KESIAPAN PEMEKARAN WILAYAH: ANALISIS SPASIAL AKSESIBILITAS DAN ALOKASI FASILITAS KESEHATAN DI CIREBON TIMUR - Prasetiya, Muhamad Hady; Harahap, Rina Muthia; Purnawan, Bebas (Program Studi Pendidikan Geografi Universitas PGRI Sumatera Barat, 2026)
Unequal distribution of healthcare facilities remains a challenge in achieving equitable public services, particularly in the proposed expansion area of East Cirebon Regency, West Java Province. This study aims to analyze the spatial distribution pattern and service coverage of hospitals and public health centers using spatial analysis methods. The applied methods include Average Nearest Neighbor (ANN) to identify distribution patterns, Kernel Density to analyze settlement density, Network Analysis (Service Area) to evaluate accessibility based on distance and travel time, and Location-Allocation to determine optimal service coverage. Spatial data consisting of administrative boundaries, settlements, road networks, hospitals, and public health centers were processed using ArcGIS 10.8. The ANN results indicate a dispersed distribution pattern with a ratio value of 1.264 (Z-score 2.57; p-value 0.009915). Service area analysis shows that healthcare facilities cover 66.55% of the area within a 6,000-meter radius, while 33.45% remains underserved. Travel-time analysis reveals uneven accessibility influenced by road network limitations. Location-Allocation analysis indicates that 77.87% of residential buildings are optimally served within a 15-minute emergency travel time. Overall, although healthcare facilities are relatively well distributed, alignment with settlement density and road accessibility remains suboptimal, highlighting the need for improved spatial planning to support regional expansion readiness.